Acute severe hypoxia induces apoptosis of human pluripotent stem cells by a HIF-1α and P53 independent mechanism - Sofía Mucci; Luciana Isaja; María Soledad Rodríguez-Varela; Sofía Luján Ferriol-Laffouillere; Mariela Marazita; Guillermo Agustín Videla-Richardson; Gustavo Emilio Sevlever; María Elida Scassa; Leonardo Romorini (Scientific Reports, 2022)
Abstract Human embryonic and induced pluripotent stem cells are self-renewing pluripotent stem cells (hPSCs) that can differentiate into a wide range of specialized cells. Although moderate hypoxia (5% O2) improves hPSC self-renewal, pluripotency, and cell survival, the effect of acute severe hypoxia (1% O2) on hPSC viability is still not fully elucidated. In this sense, we explore the consequences of acute hypoxia on hPSC survival by culturing them under acute (maximum of 24 h) physical severe hypoxia (1% O2). After 24 h of hypoxia, we observed HIF-1α stabilization concomitant with a decrease in cell viability. We also observed an increase in the apoptotic rate (western blot analysis revealed activation of CASPASE-9, CASPASE-3, and PARP cleavage after hypoxia induction). Besides, siRNA-mediated downregulation of HIF-1α and P53 did not significantly alter hPSC apoptosis induced by hypoxia. Finally, the analysis of BCL-2 family protein expression levels disclosed a shift in the balance between pro- and anti-apoptotic proteins (evidenced by an increase in BAX/MCL-1 ratio) caused by hypoxia. We demonstrated that acute physical hypoxia reduced hPSC survival and triggered apoptosis by a HIF-1α and P53 independent mechanism.